Cocoa Consumption and Blood Pressure in Middle-Aged and Elderly Subjects: a Meta-Analysis - Jafarnejad, Sadegh; Salek, Mina; Clark, Cain C. T. (Current hypertension reports, 2020)
Purpose of Review The effect of cocoa consumption on blood pressure (BP) has been investigated in previous studies; however, to date, no meta-analysis has been conducted specific to middle-aged and elderly subjects. Thus, the aim of the present study was to evaluate the effect of cocoa consumption on indices of blood pressure, in middle-aged and elderly subjects. Recent Findings Pubmed/Medline™, Cochrane Library™, Google Scholar™, and Scopus™ were searched until March 2019. The quantitative Jadad scale was used as the systematic assessment of bias in the included trials. We used a random effects model to estimate the pooled weighted mean differences (WMDs) with 95% confidence intervals (CIs). We further conducted sensitivity analysis and stratified analysis by baseline blood pressure, follow-up duration, and mean age. Thirteen studies with 758 total participants were included in the present meta-analysis. A significant reduction in SBP by 2.77 (95% CI − 5.28, − 0.27, P = 0.03, I 2 = 89%) and DBP by 1.47 mm/Hg (− 95% CI − 2.40, − 0.55, P = 0.001, I 2 = 45%) were observed after cocoa consumption. Stratified analyses showed BP-lowering effects of cocoa consumption in longer-term duration and hypertensive subgroups. Summary Our meta-analysis showed a significant inverse association between cocoa consumption and SBP/DBP. However, the analysis could not conclude any beneficial effect of cocoa consumption on blood pressure in normotensive/elevated blood pressure subjects. Therefore, further studies are warranted to affirm the efficacy of cocoa consumption for the improvement of blood pressure in elderly subjects.